(3ebGdI aj NWC ef bGd Cf cejI LhgQ hef bGd Cf TF gh LhgQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd Cf bhefG deG GTcd Ydjge abd Cf GdaUhd GdHSjWI GdebheI ddCfhGY GdLhgQjI eKd GdefWb eKdkG s
(3BNQgG (B:s
(3hdcf dGf UhQI CNQi CYOeJ gPg GdUhQI abdJ ai GdCbGeI aYdgG hgPG cGa JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs